New ways to inspect railway axles: From simulation to experimental validation. (July 2021) - Lanzagorta, J.L.; Aizpurua, I.; Vázquez, P. Ruiz; Castro, I.
Abstract: The railway industry is faced with the challenge to find adequate means to ensure absence of defects during manufacturing of axles. The use of modelling techniques has seen a rise in industry for the design of new inspection systems that can increase the capacity of complete or even substitute current inspection protocols. This study proposes two new alternative strategies based on Ultrasonic (UT) and Eddy Current Array (ECA) techniques to inspect railway axles during the manufacturing phase. Simulation models have been developed by CIVA to design and understand these new inspection procedures that increase the probability of detection (POD) and reliability of the axle. The simulations have been validated with experimental tests that have demonstrated the advantages of the use of the present approach. As a result, new inspection system concepts are presented for the inspection of railway axles.